IMPLEMENTASI MODEL PENILAIAN KINERJA BERBASIS KNOWLEDGE MANAGEMENT SCORE CARD GUNA MENINGKATKAN KUALITAS DAN KEMANDIRIAN LEMBAGA KEUANGAN MIKRO BKAD DI JAWA TIMUR - Yuntawati Fristin; Fajar Supanto; Umu Khouroh (University of Merdeka Malang, 2016)
Knowledge management as the process by which organizations accumulate intellectual capital and use it to gain competitive advantage. When organizations make a huge investment to intellectual assets, the organiza-tion must be able to measure the impact of knowledge management (KM) to the organization (tangible out-comes) and is confident that by the organization in order to collect the knowledge assets in line with the vision of the organizations mission. The objective of the research is to develop and test-development model of performance-based Knowledge Management (KM) Scorecard well as formulate a program for the development of BKAD based on intellectual capital owned.To achieve the objective, the research is carried out with the approach of participant observation. The result indicates that the assessment of KM scorecard in general provides adequately fine results when they are seen from four perspectives, those are intellectual, social, structural and humanity. The activities of human resource development (PSDM), natural resource develop-ment (PSDA), and economic resource development (PSDE) have resulted in economic increase, knowledge and skill increase, and have opened job opportunities and foster entrepreneurship opportunity. Seen from business development of real sector, BKAD has succeed to develop business of real sector based on areal resources which is in accordance with its regional potency.